The Atmanirbhar Bharat : Indigenization for Defence Forces - Ashok Kumar Panda (PREPARE@u® | IEI Conferences, 2021)
Self sustenance in terms of  ‘ Atmanirbhar Bharat’ is a delayed need for Indian subcontinent. The slogan of “Make in India” and the reality of “Made in India” are the matter of intensive realization for actual need based implementation. A missing link between above two realities are visible on ground. Professional affiliation with national and international institutions, capital expenditure for capacity enhancement in terms of machineries, test equipments and single window hassle free clearance are the challenges encountered by Atmanirbhar Bharat Aviyan in general and indigenization program for defence sectors in particular. Transfer of Technology (ToT), Memorandum of Understanding (MoU) with Original Equipment Manufacturers (OEMs) for sustenance,  Capacity Requirement Planning (CRP) , Research and Development (R&D) entities for time bound desired deliverables are the critical issues of ‘Atmanirbhar Bharat’ realization. Vendor developments, Affillate Marketing, Automation and Modernization of industries, Adoption of  IoTs, uses of  AI & ML with effective data analytics  are key criteria of success to Indinigesation for Defence forces in particular. Under ‘Atmanirbhar Bharat’ program. Additive manufacturing, 3 D printing, non conventional machining , global marketing , alternative fuel source identification and Industry-Academia integration for research advancement for gap filling with respect to conventional entities like CSIR, DRDO,RDSO and others.